Anaerobic work capacity's contribution to 5-km-race performance in female runners - Baumann, C. W.; Rupp, J. C.; Ingalls, C. P.; Doyle, J. A. (International Journal of Sports Physiology and Performance, 2012)
Purpose: The purpose of this study was to examine the relationship between anaerobic characteristics and 5-km-race performance in trained female cross-country runners (N = 13). Methods: The runners performed 50-m sprints and a 5-km time trial on an outdoor 400-m track and maximal anaerobic (MART) and aerobic running tests on a motorized treadmill. Anaerobic characteristics were determined by the mean velocity of the 50-m sprint (v50m) and the peak velocity in the MART (vMART). The aerobic characteristics were obtained during the aerobic treadmill test and included maximal oxygen uptake (VO2max), running economy, and ventila- tory threshold (VT). Results: Both the vMART (r = .69, P < .01) and VO2max (r = .80, P < .01) correlated with the mean velocity of the 5-km (v5km). A multiple-linear-regression analysis revealed that the combination of VO2max, vMART, and VT explained 81% (R2 = .81, P < .001) of the variation seen in the v5km. The vMART accounted for 31% of the total shared variance, while the combination of VO2max and VT explained the remaining 50%. Conclusions: These results suggest that among trained female runners who are relatively matched, anaerobic energy production can effectively discriminate the v5km and explain a significant amount of the variation seen in 5-km-race performance.